Acute Limb Ischemia after Cardiovascular Surgery: A Deadly Duo Combination with High Mortality - Indriani, Suci; Dewangga, Raditya; Adiarto, Suko; Siddiq, Taofan; Dakota, Iwan; Andriantoro, Hananto; Vuylsteke, Marc (International Journal of Angiology, 2023)
Acute limb ischemia (ALI) is a predictor of high morbidity and mortality. Previous studies showed that ALI developed after cardiac surgery may increase mortality.This study aimed to elucidate the clinical course and identify risk factors contributing to mortality in patients with ALI after cardiovascular surgery.This is a single-center retrospective cohort study. We analyzed data from 52 patients with ALI after cardiovascular surgery between 2016 and 2020. We evaluated the risk factors for 1-year mortality using Cox proportional hazards regression analysis.Most of the patients with ALI were male and the median age was 56 years (23–72 years). Most of the patients with ALI had coronary artery diseases. The 1-year mortality rate was 55.8% (n = 29 patients). Multivariable analysis revealed that cardiopulmonary bypass (CPB) time ≥ 100 minutes (hazard ratio [HR]: 3.067, 95% confidence interval [CI]: 1.158–8.120) and postoperative acute kidney injury (HR: 2.927, 95% CI: 1.358–6.305) were significantly increasing the risk of mortality in patients with ALI after an operation. ALI after cardiovascular surgery was associated with high 1-year mortality in our study and long CPB time and postoperative acute kidney injury contributed to the mortality.
Keywords: acute limb ischemia; cardiovascular surgery; mortality